Compression use during an exercise intervention and associated changes in breast cancer–related lymphedema. Issue 3 (3rd March 2016) - Singh, Ben; Buchan, Jena; Box, Robyn; Janda, Monika; Peake, Jonathan; Purcell, Amanda; Reul‐Hirche, Hildegard; Hayes, Sandra C
Abstract: Aim: This study assessed the association between compression use and changes in lymphedema observed in women with breast cancer–related lymphedema who completed a 12‐week exercise intervention. Methods: This work uses data collected from a 12 week exercise trial, whereby women were randomly allocated into either aerobic‐based only ( n = 21) or resistance‐based only ( n = 20) exercise. Compression use during the trial was at the participants discretion. Differences in lymphedema (measured by lymphedema index [L‐Dex] score and interlimb circumference difference [%]) and associated symptoms between those who wore, and did not wear compression during the 12‐week intervention were assessed. We also explored participants' reasons surrounding compression during exercise. Results: No significant interaction effect between time and compression use for lymphedema was observed. There was no difference between groups over time in the number or severity of lymphedema symptoms. Irrespective of compression use, there were trends for reductions in the proportion of women reporting severe symptoms, but lymphedema status did not change. Individual reasons for the use of compression, or lack thereof, varied markedly. Conclusion: Our findings demonstrated an absence of a positive or negative effect from compression use during exercise on lymphedema. Current and previous findings suggest the clinical recommendation that garments must be worn during exercise is questionable, and its application requires an individualized approach.